A Novel Bioremediation Technique for Petroleum Hydrocarbons by Bacterial Consortium Immobilized on Goethite-chitosan Nanocomposite. Issue 2 (17th February 2022) - El-Sheshtawy, H.S.; Aman, D.; Nassar, H. N.
ABSTRACT: Environmental pollution by petroleum hydrocarbon is one of the significant concerns of the contemporary world. This paper deals with the relevant environmental issues concerning the oil pollution of the petroleum industry. There is a need for further development of sustainable remediation technologies. Nineteen petroleum-degrading bacteria were isolated from an oil-polluted soil in the Suez oil processing company in Egypt. However, two bacterial species showed the highest growth rate of oil hydrocarbons. These isolates were identified by 16S rDNA gene sequence analysis into Flavobacterium johnsoniae BS1 (NCBI Gene Bank Accession no. MT740243) and Shewanella baltica BS2 (NCBI Gene Bank Accession no. MT740157). Ionic liquids prepared the goethite-chitosan nanocomposite assisted synthetic hydrothermal method. The antibacterial activity of synthesized nanocomposite on BS1and BS2 was determined. The two oil-degrading bacterial strains were immobilized onto the surface of the prepared nanocomposite. Pure and bacterial consortium studied the bioremediation process without/with nanocomposite. The remaining oil after bioremediation was extracted. Study results demonstrated that the affinity between the surface of bacterial cells and the prepared nanocomposite was investigated using scanning electron microscopy (SEM). From the antibacterial activity test of nanocomposite, there is no toxic effect on the two biodegrading microorganisms. The remaining oil after biodegradation showed that immobilized bacterial consortium achieved the maximum degradation efficiency 93.32% after 3 days of incubation. Biodegradation of different polyaromatic hydrocarbons was also studied, and immobilized bacterial consortium showed good biodegradation capabilities compared to those of free and pure cells. The nanocomposite catalyst increases the microbiological reaction rates by stimulating the activity of microbes during the biodegradation process. With this excellent biodegradation efficiency, these results suggested that the immobilized BS1 and BS2 consortium entailed high potential treatment for industrial applications for the biodegradation of oil-contaminated soil.